Strategi Pemasaran dalam Memperluas Pangsa Pasar PT Astra Daihatsu: Kajian terhadap Implementasi Digital Marketing dan Relationship Marketing - Nur Mentari; Deri Monata; Rika Mitaliani (Suria Academic Press, 2026)
Changes in consumer behavior and the rapid advancement of digital technology have encouraged automotive companies to adopt more adaptive marketing strategies to maintain competitiveness and expand market share. This study aims to analyze the implementation of PT Astra Daihatsu's marketing strategy in expanding its market share through a conceptual review approach. The study employed a conceptual review method by examining relevant literature on digital marketing, Relationship Marketing, marketing mix, customer experience, and market expansion. The sources consisted of scientific journal articles, academic books, industry reports, and official publications, primarily published between 2021 and 2025. The analysis was conducted through literature identification, thematic classification, and conceptual synthesis to develop a comprehensive understanding of PT Astra Daihatsu's marketing strategy. The findings indicate that the integration of digital marketing, Relationship Marketing, and the marketing mix enhances brand awareness, customer experience, customer satisfaction, and customer loyalty, thereby contributing to sustainable market expansion. Digital transformation through social media, corporate websites, mobile applications, and technology-based after-sales services has become a strategic factor in strengthening long-term customer relationships. Theoretically, this study reinforces the perspectives of Marketing 5.0 and Relationship Marketing by proposing a conceptual synthesis of integrated marketing strategies for market expansion. Practically, the findings provide valuable insights for automotive companies in developing adaptive, innovative, and customer-oriented marketing strategies to respond effectively to the dynamics of the digital business environment.